(untitled) (New York, 2001)
Tackles the complex environmental issue of Indoor Air Quality (IAQ) for industrial hygienists, HVAC engineers, architects and anyone else concerned with the air quality of interiors, Infused with charts, tables, and all the major formulas and calculations necessary to monitor and characterize a particular environment.
Keywords: Housing and health,Indoor air pollution